Removal of Methylene Blue by Granitic Residual Soil Supported Nano Zero Valent Iron (Gr-nZVI): Kinetic and Equilibrium Studies - Zarime N.A.; Solemon B.; Yaacob W.Z.W.; Jamil H.; Omar R.C.; Wahab W.A.; Isa A.A.M. (Elsevier B.V., 2025)
The presence of dyes in water sources that act as contaminants is hazardous to human and animal health. Therefore, this research was conducted on the removal of methylene blue (MB) using granitic residual soil-supported nano zero-valent iron (Gr-nZVI), to examine its potential use as an efficient adsorbent. Batch adsorption experiments were conducted in this study to examine the impact of initial dye concentration, contact time, dosage, pH and temperature effets. Based on the results, it can be inferred that Gr-nZVI (with Kd=0.1 L/g and R2 =1) exhibits superior adsorption of MB at higher metal ion concentrations when compared to granitic residual soil (Gr) (with Kd=0.0588 L/g and R2 =0.9267). The removal percentage of Gr-nZVI was found to be 100%, obtained at 100 mg/L MB ion concentration. Sorption data have been correlated with both Langmuir and Freundlich adsorption models. However, the Langmuir isotherm was the only model that showed a good fit for the adsorption of MB on Gr-nZVI. The mechanistic phases of the process were determined through kinetic energy studies. Kinetic data showed the removal of MB was 100% within 5 min for both Gr-nZVI and Gr. This indicates the very fast adsorption of MB and data followed a pseudo-second order. According to adsorption analysis, Gr demonstrated a higher adsorption capacity for MB removal compared to Gr-nZVI and nZVI. This study also highlights that nZVI does not facilitate MB adsorption, making the composite nZVI unnecessary due to Gr is capable of removing MB on its own. ? 2024 The Authors